Grapes and Health - Pezzuto, John M. (Springer International Publishing : Imprint: Springer, 2016)
This book offers a thorough review of the scientific research that links the consumption of grapes to better health. The book starts with a basic review of grape biology, including the key families of phytochemicals found in grapes, and where they are found. An overview of the rationale for and subsequent creation of a standardized grape powder for use in basic and clinical research provides insight and understanding regarding its widespread use in grape-specific research today. The remaining chapters each thoroughly examine a key area of health, demonstrating a significant scope of impact on well-being. The book examines the role of grapes in supporting heart health under multiple angles: general cardiovascular effects, as well as specific effects directly linked to atherosclerosis and hypertension. Other emerging and important areas of health are examined, ranging from grapes and cancer, where grape consumption has been shown to protect healthy colon tissue; grapes andinflammation, where grapes have been shown to block inflammatory activity in immune cells of fat tissue; to brain health, where a grape-enriched diet has been shown to protect against neuronal damage due to loss of oxygen in the brain, as well as against oxidative stress-related anxiety and resulting memory loss; to grapes and eye health where grape consumption has been shown to protect the retina from damage.